Collectible toys - fatores influenciadores e resultantes do colecionismo: um estudo com colecionadores de estátuas e figuras de ação brasileiros e norte-americanos - Silva, Helder Haddad Carneiro da (2018)
Collecting as a consumer phenomenon has been studied from different perspectives, and its antecedent and consequent factors are vast and complex. This thesis brings as an original academic contribution the establishment of positive and significant theoretical relations between factors influencing and resulting from the collecting practice that stand out in the existing literature, arguing that positive emotional factors influence the thematic interest of the collector, which in turn provides emotional well-being and suppression of frustration, expansion and extension of the self and feelings of personal nostalgia. In order to meet the objective of investigating the correlations between the proposed constructs, a mixed methodological approach was adopted. The bibliographic survey served as a theoretical basis for the definition of hypotheses and the design of a conceptual model. The exploratory qualitative research carried out with five opinion leaders linked to the thesis’ object of study - the collectors of statues and action figures - consolidated an understanding about the motivators involved in this type of collection. Quantitative descriptive research occurred in three distinct phases. At first, scales were developed and adapted following recommended psychometric procedures. A sample with 250 collectors was used as a pre-test in order to determine the measurement model. After the validation and evaluation of the reliability of the scales, the theoretical relations hypothesized were analyzed by means of confirmatory factor analysis and structural equations modeling based on PLS. Two surveys were carried out with collectors of statues and action figures, one in Brazil, with a sample of 700 collectors, and another in the United States, with a sample of 250 collectors, comparing the results of the measurement and structural models. The results indicate that early positive emotions influence the thematic interest of the collector, leading him to collect as a form of identity expression (extension of the self) and search for the expansion of the self (expanded self), through the possession of collection objects, with effect on the individual's emotional wellbeing. Extended Self and Expanded Self constructs prove distinct in their conceptual perspectives. In addition, the age group is shown as an important moderating variable in the relationships between suppression of frustration and personal nostalgia - the objects of collection evoke memories and nostalgic feelings and play a compensatory role. On the other hand, the origin of the collectors (Brazil and USA) does not appear as a moderating variable of the predicted theoretical relations, which indicates indistinct influencing and resulting factors. As a general conclusion, the thesis offers a way for the construction of a theory on collectivism, with an unprecedented and initial understanding of relevant causal relations.